Poverty level grouping using SAW method - Yunaeti Anggraeni, Elisabet; Huda, Miftachul; Maseleno, Andino; Safar, Jimaain; Azmi Jasmi, Kamarul; Kilani Mohamed, Ahmad; Hehsan, Aminudin; Basiron, Bushrah; Suhaila Ihwani, Siti; Hassan Wan Embong, Wan; Marzuki Mohamad, Ahmad; Shakib Mohd. Noor, Sulaiman; et al. (International Journal of Engineering and Technology, 2018)
Poverty is social gap problem for some people with below average income level but in Pringsewu district the poverty rate is significantly decreased so it is expected to increase the potential of Pringsewu region to be better, in increasing the potential of the region it needs a system that is expected to assist in determination of poverty level in sub district in Pringsewu by data clustering and ranking from every subdistrict in Pringsewu Regency using SAW method. Therefore, we are interested to build an application of Poverty Grouping in Pringsewu region in the form of Poverty Index of the last few years, existing data is expected to be a reference to increase the potential of the area by reducing the poverty rate every year. It is expected that the data obtained can be a reference of the government in reducing poverty level in subdistrics in Pringsewu District.Â Â
Keywords: Decision Support System; Poverty; Simple Additive Weighting; Criteria.